A CASE OF URBAN MIMICRY: CITRA RAYA, THE SINGAPORE OF SURABAYA - Dyah Erti Idawati (Journal of Architecture&ENVIRONMENT, 2015)
Under the forces of globalization, there is considerable pressure for cities to enhance their attractiveness in numerous ways in order to attract capital. Surabaya, Indonesia’s second largest city, promotes a strategy to match the aesthetic criteria associated with imagined global metropolises. Singapore has been extremely influential in inspiring other cities in the South East Asian region and a dream to be another Singapore certainly appears in Surabaya.  Imitating Singapore’s gleaming towers and exotic waterfront, Surabaya has sought to eliminate backward scenes including more traditional settlement forms. Interestingly, this trend to create an image of Singapore is not only supported by the business community but by the Surabaya’s government as well.  This paper explores how the image of Singapore has influenced the shape of Surabaya in both systematic and practical ways, particularly addressing to what extent this obsession with Singapore has affected Surabaya images and identities?